Individual choice and reputation distribution of cooperative behaviors among heterogeneous groups. (August 2015) - Lu, Peng
Highlights: Cooperation macrocosmically refers to the overall cooperation rate, while reputation microcosmically records individual choices. Therefore, reputation should be preferred in order to investigate how individual choices evolve. Both the mean and standard deviation of reputation follow clear patterns, and some factors have quadratic effects on them. Abstract: Cooperation is vital for our society, but the temptation of cheating on cooperative partners undermines cooperation. The mechanism of reputation is raised to countervail this temptation and therefore promote cooperation. Reputation microcosmically records individual choices, while cooperation macrocosmically refers to the group or averaged cooperation level. Reputation should be preferred in order to investigate how individual choices evolve. In this work, we study the distribution of reputation to figure out how individuals make choices within cooperation and defection. We decompose reputation into its mean and standard deviation and inspect effects of their factors respectively. To achieve this goal, we construct a model where agents of three groups or classes play the prisoners' dilemma game with neighbors on a square lattice. It indicates in outcomes that the distribution of reputation is distinct from that of cooperation and both the mean and standard deviation of reputation follow clear patterns. Some factors have negative quadratic effects on reputation's mean or standard deviation, and some have merely linear effects.